![Slide41.JPG](https://cdn.teachoo.com/a9e3f065-79a7-43b1-a916-ba6ead05268a/slide41.jpg)
![Slide42.JPG](https://cdn.teachoo.com/6c0f48ef-2374-4319-8661-cbf4ea893f39/slide42.jpg)
![Slide43.JPG](https://cdn.teachoo.com/0cc025b1-08bf-4829-b20f-7eddeab13e0d/slide43.jpg)
![Slide44.JPG](https://cdn.teachoo.com/e4c6ef0a-e2d9-43c5-a0ad-4e6e2b3132be/slide44.jpg)
![Slide45.JPG](https://cdn.teachoo.com/ac9095b5-e1f5-4688-b3d5-e2c057e3254e/slide45.jpg)
![Slide46.JPG](https://cdn.teachoo.com/7f757ec8-c010-4a40-b7fb-dab85ba33259/slide46.jpg)
![Slide47.JPG](https://cdn.teachoo.com/784edf22-327f-4b3a-98b7-dc78f345e172/slide47.jpg)
![Slide48.JPG](https://cdn.teachoo.com/1f01c6ac-f440-4b22-b977-8316f3e9a840/slide48.jpg)
![Slide49.JPG](https://cdn.teachoo.com/32cd5b14-4a2a-4671-97eb-6ae93808bbb5/slide49.jpg)
Examples
Last updated at Dec. 16, 2024 by Teachoo
Example 41 (Introduction) Evaluate β«_(β1)^(3/2)β|π₯ sinβ‘(π π₯) | ππ₯ To find sign of |π₯ sinβ‘(π π₯) | in the interval, let us check sign of x and sinβ‘γ (ππ₯) γseparately π₯ > 0 & π₯ sinβ‘γ (ππ₯) γ> 0 π₯ < 0 & π₯ sinβ‘γ (ππ₯) γ> 0 Sign of x We have Interval β1< π₯ < 3/2 Sign of π¬π’π§β‘γ(π π)γ Here, β1β€π₯β€3/2 βπ β€ππ₯β€3π/2 Let π=ππ₯ β΄ βπ β€ΞΈβ€3π/2 From graph it is seen, Now, Sign for π₯ sinβ‘(ππ₯) in interval β1 β€ x β€ 3/2 is So, we can write |π₯ π ππ (Οπ₯)|={β(π₯ sinβ‘γ (ππ₯)γ β1 β€ π₯ β€ 1@&βπ₯ sinβ‘γ (ππ₯)γ 1 β€ π₯ β€ 3/2)β€ Example 41 Evaluate β«_(β1)^(3/2)β|π₯ sinβ‘(π π₯) | ππ₯ Solving β«1βγπ πππβ‘γ (π π) π πγ γ separately β«1βγπ₯ sinβ‘γ (ππ₯) ππ₯γ γ = x β«1βsinβ‘γ(ππ₯)ββ«1β(π(π₯)/ππ₯ β«1βsinβ‘γ(ππ₯) γ ) γ ππ₯ = x ((βcosβ‘γ(ππ₯))γ)/πββ«1β1((βcosβ‘γ(ππ₯)γ)/π) ππ₯ = (β π₯ cosβ‘γ(ππ₯) γ)/π+β«1βcosβ‘γ(ππ₯)γ/π ππ₯ = (βπ₯ cosβ‘γ(ππ₯)γ)/π+ sinβ‘γ(ππ₯)γ/π^2 β«_(βπ)^πβγπ π¬π’π§β‘γπ π π πγ γ = [(βπ₯ cosβ‘γ(ππ₯)γ)/π+sinβ‘γ(ππ₯)γ/π^2 ]_(β1)^1 = ((β1 cosβ‘π)/π+sinβ‘π/π^2 ) β((β(β1)cosβ‘γ(βπ)γ)/π+sinβ‘γ(βπ)γ/π^2 ) = ((β1 Γ (β1))/π+0/π^2 ) β(cosβ‘π/π+γβ sinγβ‘π/π^2 ) = (1/π+0)β((β1)/π+0) = 1/π+1/π = 2/π Putting limits β«_π^(π/π)βγπ π¬π’π§β‘γπ π π πγ γ = [(βπ₯ cosβ‘γ(ππ₯)γ)/π+sinβ‘γ(ππ₯)γ/π^2 ]_1^(3/2) = (((β3)/2 cosβ‘(3π/2))/π+sinβ‘((3π )/2)/π^2 )β((β1 cosβ‘π)/π+sinβ‘π/π^2 ) = (0+((β1))/π^2 )β((β1 Γ β1)/π+0/π^2 ) = (β1)/π^2 β1/π Now, β΄ β«_(β1)^(3/2)β|π₯ sinβ‘(ππ₯) | ππ₯ = β«_(β1)^1βγπ₯ sinβ‘γ (ππ₯) ππ₯ ββ«_1^(3/2)βγπ₯ π ππγγ γ(ππ₯) ππ₯ = 2/πβ((β1)/π^2 β1/π) = 2/π+1/π^2 +1/π = π/π +π/π ^π